Relationship between nutritional status, anthropometric measurements and dietary inflammatory index in professional football players - EREN, FATİH (My University, 2023)
Objective: This study was carried out to evaluate the relationship between the nutritional status, anthropometric measurements and dietary inflammatory index (DII) of professional football players exposed to long-term intense exercise. Method: Twenty-one professional male football players with a mean age of 26.00 +/- 5.69 years playing in the same club participated in the study. The nutritional status of the football players was evaluated with 3-day food consumption record (2 days of training and 1 match day). DII scores were calculated using data on 34 nutrient/nutritional ingredients obtained from the food consumption records. Body fat percentage in the anthropometric evaluations were determined by caliper and skinfold thicknesses. Results: The median DII scores of the football players were found as - 3.42 (-9.95 - 0.95), and their nutritional intake were found to be anti-inflammatory. When the relationship between the DII scores of the football players and their anthropometric measurements was examined, a positive and significant correlation (R: .476; p: .029) was found between their DII score and their abdominal adiposity. However, there was no significant correlation (p> .05) between the DII scores and the other anthropometric measurements. In addition, there was a significant negative correlation (R: - .468; p: .032) between fiber consumption and abdominal adiposity, and a significant positive correlation between carbohydrate and fat consumption and body weight (respectively R= .730 p= .000; R= .526 p= .014). Conclusion: It has been revealed that the football players participating in our study generally have an anti-inflammatory diet. It was also found that abdominal adiposity was higher in the football players with high DII scores.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Football player; dietary inflammatory index; anthropometry; SOCCER PLAYERS; BODY-COMPOSITION; ENERGY-INTAKE; FAT; EXPENDITURE; MASS; Football player; dietary inflammatory index; anthropometry